Academic connotation and research trends of privacy computing - Fenghua LI; Hui LI; Ben NIU; Weidong QIU (网络与信息安全学报)
The authors of this paper first proposed the concept, definition and academic connotation of privacy computing, and formed a relatively mature theoretical and technical system accordingly.In order to continuously promote the academic research and industrial application of privacy computing, the academic connotation of privacy computing was elaborated, including how to understand the full-life cycle, extended control, privacy quantification and mapping, desensitization effect evaluation.Besides, the necessity of iterative on-demand desensitization and the motivation to study the language of privacy computing were presented.The role of audit log self-storage in ubiquitous sharing was explained and some distorted academic concepts were also clarified.Moreover, 37 research points in 9 aspects of privacy computing and 40 research points in 8 aspects of data security were given.It helps to better understand the research scope of privacy computing and correctly distinguish between privacy computing and data security.